2002
DOI: 10.1111/j.1547-5069.2002.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Attitudes Toward Advance Directives

Abstract: Patients' attitudes alone did not determine who will and will not complete advance directives. Most participants who completed advance directives had specific reasons for doing so. Nurses have responsibility for discussing advance directives with patients, families, and physicians to ensure adequate education about the completion of advance directives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 18 publications
6
64
3
1
Order By: Relevance
“…4 Our findings indicate that preparedness planning initiated during a palliative care consultation may be a necessary first step to the ultimate completion of an AD, but more importantly, to respecting patients' wishes and preferences the next time they are admitted to the hospital.…”
mentioning
confidence: 74%
“…4 Our findings indicate that preparedness planning initiated during a palliative care consultation may be a necessary first step to the ultimate completion of an AD, but more importantly, to respecting patients' wishes and preferences the next time they are admitted to the hospital.…”
mentioning
confidence: 74%
“…Studies have indicated that, in general, patients believe they should be given choices about the care they receive at the end-of-life. A study of attitudes about advance directives among a sample of 30 inpatients by Douglas and Brown (2002), reported that all thirty participants believed they would be given such choices, while 29 said that, if they were unable to make such choices, their family members would be given the opportunity. In a 2000 study of 1,016 randomly drawn patients from four tertiary hospitals, the most frequently cited reason respondents gave for having a directive was "wanting to make up your own mind" (92%) (Mezey et al, 2000).…”
Section: Review and Critique Of Related Studiesmentioning
confidence: 99%
“…Furthermore, the respondents reported that they felt more comfortable discussing advance directives with an attending physician (94%) or nurse (78%), versus other hospital personnel (39%). Douglas and Brown (2002) found that of their sample of thirty hospital patients, only 18% of the seventeen who didn't complete advance directives listed "discomfort with making decisions about life support" as a reason (p. 64). Although a study of 55 adults aged 50 years or older by Inman (2002) did find a degree of patient discomfort with discussing advance directives with statements such as "it's too morbid" and "I can't cope with the thought of death" (p. 44), these reasons fell behind less emotional ones such as "haven't gotten around to it" and "not ready" (p. 44) and were taken from a minority 22% who had not discussed end-of-life wishes with someone.…”
Section: Review and Critique Of Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Natural Death Act, first passed in California, USA, in 1976, initiated living wills, and some forms of the act have now been implemented in most of the United States and Canada [1,2,3]. By signing living wills, incurable and terminal patients record their last decisions, primarily to refuse or accept cardiopulmonary resuscitation (CPR).…”
Section: Introductionmentioning
confidence: 99%